Administrative barrier and career advancement of female academic staff in Nigerian Universities - Hassan, Abubakar Idris; Baharom, Mohd Nazri; Abdul Mutalib, Rozita (Society of Scientific Research and Education (SSRE), 2016)
Female participation in formal sector is increasingly growing in both male and female oriented organizations around the world.However, the degree at which female are represented in the higher level of their career is discouraging, especially in Nigerian universities. Using thematic analysis via NVivo 10 software in analyzing interviews conducted on female academic staff.This study has therefore, explore and found that administrative factor; such as excessive workload and lack of political will were barriers to the career advancement of female academic staff in the Nigerian universities.